Could EGM player-tracking systems help link gamblers to treatment services in Australia: a thematic analysis of counsellor and community educators' perspectives. Issue 3 (2nd September 2017) - Langham, Erika; Rockloff, Matthew; Browne, Matthew; Best, Talitha
Abstract: There are a number of different pathways to care that people experiencing problems with gambling may pursue. The current research examined the potential of player-tracking systems, such as pre-commitment technology or loyalty cards, to improve the delivery of links to treatment. Thirty-three key informants from gambling treatment and community education in Australia were interviewed about the potential contributions of these technologies to helping link gamblers with problems to treatment services. Thematic analysis revealed three broad considerations for effective links to treatment using these technologies. First, links need to be appropriate in terms of the multitude of problems (other than gambling) that people might face with customized links appropriate to a gambler's circumstances. Second, the presentation of the links should make them easy to notice and appropriately timed. Third, links should be provided as part of a broader strategy of harm minimization; by recognizing where people are in terms of behavioural change; providing positively framed guidance; and maintaining consistency with public health approaches. This research provides guidance based on informed expert opinion on what features of technology-driven links-to-treatment are likely to meet with greatest success.